THE ARABIC LANGUAGE AND ISSUES OF CULTURAL IDENTITY: CHADIAN POETRY AS A MODEL-AN ANALYTICAL DESCRIPTIVE STUDY - Dr. Mohamed Mokhtar Ahmed Khayar; Dr. Bashir Mohamed Ishaq; Dr. Mohamed Ahmed Mohamed (Scholars Digest Publishing, 2025)
This study responds to the call of the Conference on the Arabic Language: Between Heritage and Modernity, held under the auspices of the College of Arts at the University of Al-Qadisiyah. The researchers contributed a paper titled "The Arabic Language and Issues of Cultural Identity: Chadian Poetry as a Model – An Analytical Descriptive Study. The study seeks to answer key questions arising from its central theme: Are there sufficient poems or passages in Chadian Arabic poetry that address the Arabic language and issues of cultural identity? What are the main issues raised by these poets to highlight the role of the Arabic language in this context? The study offers comprehensive answers to these methodological questions by identifying poetic texts within Chadian Arabic literature that engage with themes related to the Arabic language in Chad—such as its spread, the public’s deep affection for it, its status as an official language in contrast to French, and the country’s cultural orientation towards the Arab world. The research is organized around three main axes: 1. The role of Arabic in strengthening cultural identity and promoting social cohesion. 2. The function of Arabic as a catalyst for cultural renaissance, as expressed in Chadian Arabic poetry. 3. The poetic form, including analysis of external musicality (meters and rhymes) and internal musicality (imagery, rhetorical devices, and aesthetic elements). The findings indicate that Chadian Arabic poetry plays a significant role in reinforcing cultural identity through the Arabic language. Key conclusions include:
Keywords: Arabic language – Cultural identity – Chadian poetry – Language issues